Risk factors associated to tuberculosis in Santiago de Cuba during 2007-2011 - Làzaro Ibrahim Romero Garcìa; karima Maricel Gondres Legrò; Yordanys Paez Candelaria; Pedro Alexei Bacardì Zapata; Orlys Jones Romero (Centro Provincial de Información de Ciencias Médicas, 2016)
A descriptive and cross-sectional study of 323 cases of tuberculosis estimated in Santiago de Cuba during 2007-2011, was carried out to describe the associated epidemiologic risk factors. Absolute numbers and percentages were computed. In the series the prisoners or exprisoners prevailed (28.9%), as well as the advanced age and the alcoholism as important factors (16.4 and 11.7%, respectively). It was concluded that the investigation and control of tuberculosis should be motivated in vulnerable people, with the purpose of maintaining low risks of getting sick and dying for this cause in the reference province.